Medicine and surgery in Central Asia - Stumbles, Henry Martyn (The University of Edinburgh, 1910)
Two cardinal facts exist in connection with Medicine and Surgery in Thibet and they are these:

1. There exists no definite Science, such knowledge as there is being derived from the study of old Buddhist and Sanskrit lore.

2. It is wholly controlled by religious fanaticism exerted by the influence of the Buddhist Lamas. This latter is illustrated by Photograph X. herewith (page 53.). In it is depicted a house in which sickness has occurred. In the room on the right the patient is in bed, evidently in an emaciated condition, and a priest is in the act of feeling his pulse. Outside in the adjoining room another priest sits amidst charms of all kinds - some (those on the table) being composed of butter and rice, others (on the floor) being made of cotton thread wound around a wooden frame of definite shape. The priest is sitting at his drum which he beats incessantly day and night, being relieved every few hours by another priest, All this is to keep away and drive away the Evil Spirit which is causing the sickness. For this work he receives about 1/- per day plus his food and plenty of "chang" (Thibetan beer). . When the patient is recovering, during one night at a time privately arranged by the priests, they rush about the house as if suddenly become mad and eventually, having exorcised the evil spirit which enters into some of their charms, they rush outside and burn them in a big bonfire and at the same time discharge firearms. This is the end of the case.

Unfortunately it must be many years before these things can change. Education they refuse, and as the country is over-run with Lamas any good influence brought to bear upon the layman is speedily destroyed by the action of the Lamas who call down upon the infidel all the worst maledictions possible. He in fear has perforce to amend his ways or else incur their displeasure which they do not omit to arrange shall be in a very tangible form.